Use and institutionalization of field-specific nutrient management Decision Support Tool (DST) by NARES in Tanzania and Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
To increase productivity and efficient fertilizer use, African smallholders need tailored, field-specific advice. A new mobile phone application 'Maize-Nutrient-Manager' piloted in southwestern Tanzania, resulted in ~1,000 smallholder farmers receiving field-specific, balanced nutrient management advice for their maize fields. Advice was provided by the district extension service, supported by the regional Agricultural Research Institute. Bringing this productivity-enhancing, and greenhouse gas emissions reducing, advisory tool to scale, institutionalizes field-specific advisory in national agricultural advisory systems in Tanzania and Ethiopia.